Trinuclear Copper(II) Complexes - Rai, H.C. (Asian Journal of Chemistry, 2010)
An interesting group of trinuclear copper(II) complexes have been obtained by the action of copper halides on the mononuclear complexes and charcterized on the basis of elemental analysis. spectral and electrochemical studies.